Fabrication and Nanomechanical Characterization of Thermoplastic Biocomposites Based on Chemically Treated Lignocellulosic Biomass for Surface Engineering Applications - Sulaiman, Muhammad; Iqbal, Tanveer; Yasin, Saima; Mahmood, Hamayoun; Shakeel, Ahmad (Frontiers in Materials, 2021)
Diverse applications of polymeric materials have prompted development of eco-friendly, efficient, and economical materials. These characteristics can be obtained by incorporating appropriate fillers in the polymeric matrix. The objective of this work is to investigate impact of aqueous glycerol (Gly) treated rice husk (RH) on surface mechanical properties of produced biocomposites. RH was treated with aqueous Gly (75 wt%) and compounded with low density polyethylene (LDPE) at different loadings (10, 20, and 30 wt%). The resulting mixture was thermally pressed in molds to fabricate biocomposites. Surface mechanical properties such as elastic modulus, hardness, creep rate, and plasticity of biocomposites reinforced with untreated and treated RH were investigated using nanoindenter. Experimental values depicted that hardness (H) and elastic modulus (Es) of treated biocomposites were higher than untreated ones. Treated biocomposites showed the noticeable improvement in elastic modulus by 24 and 37% compared to untreated biocomposites at 20 wt% loading and neat LDPE, respectively. Reductions in the creep rate by 20 and 14% were observed for untreated and treated biocomposites, respectively, in comparison to the neat LDPE. H/E ratio was increased by 23 and 18% for treated and untreated biocomposites, respectively, as compared to virgin LDPE. Furthermore, mechanical and structural properties of untreated and treated RH are reported based on nanoindentation response and Fourier transform infrared spectroscopy (FTIR) techniques The study indicated that aqueous glycerol pretreatment can partially strip off non-cellulosic constituents from lignocellulose matrix to generate cellulose-rich pulp for engineered composite applications.